An In Vitro Gut–Liver–Adipose Axis Model to Evaluate the Anti-Obesity Potential of a Novel Probiotic–Polycosanol Combination - Simone Mulè; Rebecca Galla; Francesca Parini; Mattia Botta; Sara Ferrari; Francesca Uberti (Foods)
The gut-liver-adipose axis plays a pivotal role in metabolic regulation, and its dysregulation contributes to obesity and metabolic syndrome. Probiotics and polycosanol have shown potential in modulating gut barrier integrity, lipid metabolism, and inflammation. This study aimed to evaluate their combined effects using an in vitro model of the gut-liver-adipose axis. Transwell® system was used to recreate the interaction between intestinal (CaCo-2), hepatic (HepG2), and adipose (3T3-L1) cells. Cells were treated with Bifidobacterium bifidum GM-25, Bifidobacterium infantis GM-21, Lacticaseibacillus rhamnosus GM-28, and polycosanols. The effects were assessed by analyzing intestinal barrier integrity (TEER, tight junction proteins), hepatic and adipose lipid accumulation (Oil Red O staining), oxidative stress (ROS production, lipid peroxidation), inflammation (TNF-α) and lipid metabolism (CD36, PPARγ, AMPK and SREBP-1 levels). Probiotics and polycosanols improved intestinal integrity, increased butyrate production, and reduced ROS levels. Hepatic lipid accumulation was significantly decreased, with enhanced PPARγ and AMPK activation. In adipocytes, probiotic-polycosanols treatment suppressed SREBP-1 expression, enhanced lipid oxidation, and promoted UCP1 and PGC-1α expression, suggesting activation of thermogenic pathways. These findings underline a possible biological relevance of probiotics and polycosanols in modulating metabolic pathways, improving gut barrier integrity, and reducing inflammation, supporting their role as functional ingredients for metabolic health.